Analisis Pendapatan Buruh Wanita Di Pasar Tradisional (Studi Kasus Di Pasar Badung) - Yoni Try Jayanti, Ni Nyoman; Sukarsa, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 4, April 2016 (pp.385 - 429), 2016)
The participation of women in the activities increased revenues can be seen from the amount of income obtained. Women's work is generally not as the main breadwinner although it is possible that the income will be very useful to support the family economy. The purpose of this study was to analyze the effect of direct and indirect labor income demographic variables against women through the allocation of work time female workers at Pasar Badung. This study using quota sampling method in data collection and analysis technique for the analysis of the data path. Based on the analysis found that age is a significant negative effect on the income of women workers in Pasar Badung while the allocation of working time and a significant positive effect on the income of women workers in Pasar Badung. The number of dependents and the allocation of working time and a significant positive effect on the income of women workers in Pasar Badung. Age and number of dependents indirect effect on labor income women through the allocation of women laborers working time in Badung market or in other words the allocation of working time is a variable mediating the effect of age and the number of dependents on labor income women through the allocation of work time.
Keywords: age; number of dependents; the allocation of work time; income of women workers